2016
DOI: 10.5433/1679-0359.2016v37n4p1997
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of teat antiseptics against Staphylococcus aureus strains isolated from bovine mastitis

Abstract: The process of teat disinfection is a widely accepted component of successful mastitis control programs by reducing the number of bacteria on the teat skin and healing teat lesions. For contagious pathogens such as Staphylococcus aureus, post-milking teat disinfection remains a simple, effective and economical practice for prevention of new intramammary infections (IMIs) of lactating dairy cows. Despite the universal acceptance of teat dipping as a method of mastitis control, variations in the susceptibility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…uberis when tested using the excised teat method (Enger et al, 2015). Furthermore, Santos et al (2016) demonstrated, in vitro, that a 2.5% chlorine dioxide product resulted in reduction levels comparable to a 0.6% iodine product at four different exposure times (15 s, 30 s, 60 s and 300 s) against 50 Sta. aureus strains.…”
Section: Discussionmentioning
confidence: 95%
“…uberis when tested using the excised teat method (Enger et al, 2015). Furthermore, Santos et al (2016) demonstrated, in vitro, that a 2.5% chlorine dioxide product resulted in reduction levels comparable to a 0.6% iodine product at four different exposure times (15 s, 30 s, 60 s and 300 s) against 50 Sta. aureus strains.…”
Section: Discussionmentioning
confidence: 95%